Insights into O-GlcNAcylation and programmed cell death in cancer - Yan, Xiaohan; Ren, Wenhao; Zhu, Zhuang; Li, Shaoming; Shi, Rui; Sun, Kai; Zhi, Keqian; Gao, Ling; Zheng, Jingjing (Frontiers in Cell and Developmental Biology, 2025)
O-GlcNAcylation is an essential post-translational modification that adds O-linked β-N-acetylglucosamine (O-GlcNAc) to numerous proteins’ serine or threonine residues. Several studies have indicated O-GlcNAcylation regulates various processes related to cancer, including signal transduction, transcription, cell division, metabolism, and cytoskeletal regulation. Programmed cell death (PCD) is a regulated and organized form of cell death controlled by genes, including apoptosis, autophagy, pyroptosis, necroptosis, and ferroptosis. As research on PCD has become increasingly in-depth, a potential link between O-GlcNAcylation and PCD has emerged. This review will focus on the complex relationships between O-GlcNAcylation and different PCD pathways, which are closely tied to the onset, progression, and resistance of cancer. By clarifying the relationship between O-GlcNAcylation and PCD, we aim to create a theoretical basis for improving anti-cancer treatments, with promising potential for clinical application.